HIV-1 Uncoating and Reverse Transcription Require eEF1A Binding to Surface-Exposed Acidic Residues of the Reverse Transcriptase Thumb Domain - Daniel J. Rawle (American Society for Microbiology, 2018)
ABSTRACT Once HIV-1 enters a cell, the viral core is uncoated by a poorly understood mechanism and the HIV-1 genomic RNA is reverse transcribed into DNA. Host cell factors are essential for these processes, although very few reverse transcription complex binding host cell factors have been convincingly shown to affect uncoating or reverse transcription. We previously reported that cellular eukaryotic translation elongation factor 1A (eEF1A) interacts tightly and directly with HIV-1 reverse transcriptase (RT) for more efficient reverse transcription. Here we report that the surface-exposed acidic residues in the HIV-1 RT thumb domain alpha-J helix and flanking regions are important for interaction with eEF1A. Mutation of surface-exposed acidic thumb domain residues D250, E297, E298, and E300 to arginine resulted in various levels of impairment of the interaction between RT and eEF1A. This indicates that this negatively charged region in the RT thumb domain is important for interaction with the positively charged eEF1A protein. The impairment of RT and eEF1A interaction by the RT mutations correlated with the efficiency of reverse transcription, uncoating, and infectivity. The best example of this is the strictly conserved E300 residue, where mutation significantly impaired the interaction of RT with eEF1A and virus replication in CD4+ T cells without affecting in vitro RT catalytic activity, RT heterodimerization, or RNase H activity. This study demonstrated that the interaction between surface-exposed acidic residues of the RT thumb domain and eEF1A is important for HIV-1 uncoating, reverse transcription, and replication. IMPORTANCE HIV-1, like all viruses, requires host cell proteins for its replication. Understanding the mechanisms behind virus-host interactions can lay the foundation for future novel therapeutic developments. Our lab has identified eEF1A as a key HIV-1 RT binding host protein that is important for the reverse transcription of HIV-1 genomic RNA into DNA. Here we identify the first surface-exposed RT residues that underpin interactions with eEF1A. Mutation of one strictly conserved RT residue (E300R) delayed reverse transcription and viral core uncoating and strongly inhibited HIV-1 replication in CD4+ T cells. This study advances the structural and mechanistic detail of the key RT-eEF1A interaction in HIV-1 infection and indicates its importance in uncoating for the first time. This provides a further basis for the development of an RT-eEF1A interaction-inhibiting anti-HIV-1 drug and suggests that the surface-exposed acidic patch of the RT thumb domain may be an attractive drug target.